2016
DOI: 10.2172/1244312
|View full text |Cite
|
Sign up to set email alerts
|

Chemicals from Biomass: A Market Assessment of Bioproducts with Near-Term Potential

Abstract: from the National Renewable Energy Laboratory (NREL) for helpful discussions, comments, and shared insights during the development of this report. We appreciate all of the help from Kathy Cisar for her technical editing and support in publishing this report. Finally, we thank Billie Christen from the NREL for her help in formatting this report and for developing the U.S. bioproduct facilities map.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
214
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(217 citation statements)
references
References 73 publications
(152 reference statements)
0
214
0
3
Order By: Relevance
“…An updated market assessment and potential of these chemicals was published in 2016 (Biddy et al 2016).…”
Section: Bio-advantaged Platform Chemicals From Woodmentioning
confidence: 99%
“…An updated market assessment and potential of these chemicals was published in 2016 (Biddy et al 2016).…”
Section: Bio-advantaged Platform Chemicals From Woodmentioning
confidence: 99%
“…The conversion of biomass into platform molecules with a broad application range has attracted a great deal of attention in the last decade [1]. One of the interesting and promising examples of a platform molecule is γ-valerolactone (GVL).…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop economically-viable biorefineries, production of value-added chemicals along with fuel is investigated by academics. Furthermore, interest in bio-based chemicals has risen due to increasing environmental problems and climate change concerns associated with the growing use of fossil resources (Bos and Sanders, 2013;Biddy et al, 2016). Bioethanol is the main product generated from sugar-based platforms, followed by n-butanol, acetic acid, and lactic acid, these occupy much smaller but still significant shares of the market though.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, succinic acid is one of bio-products, reported among the top twelve with near-term deployment potential based on its large projected . market (Biddy et al, 2016), since it has been identified as a feedstock for higher value products (Shen et al, 2015). Due to the wide spectrum of possible products from first and second generation feedstocks and the complexity of the processes involved, techno economic assessment (TEA) should be carried out to define the feasibility of the biorefineries.…”
Section: Introductionmentioning
confidence: 99%